2018
DOI: 10.3892/etm.2018.5914
|View full text |Cite
|
Sign up to set email alerts
|

β-Endorphin attenuates collagen-induced arthritis partially by inhibiting peripheral pro-inflammatory mediators

Abstract: Abstract. The classical analgesic pathway of opioids by binding their receptors in the nervous system is well known. However, little is known regarding opioid analgesia through the anti-inflammatory pathway. The present study aimed to investigate the analgesic and anti-inflammatory effect of β-endorphin on inflammatory pain. A rat model of collagen-induced arthritis (CIA) was generated by intradermal injection of bovine type II collagen. Rats were divided into the CIA + saline group and the CIA + β-endorphin g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The analgesic effects of acupuncture are likely to be correlated with the capacity of acupuncture in modulating pituitary and hypothalamic β-endorphin levels [ 8 , 44 , 76 , 88 ]. On the other hand, the analgesic and anti-inflammatory effects of β-endorphin on inflammatory pain have also been confirmed [ 27 ]. Taken together, acupuncture may play a positive role in COVID-19 associated pain.…”
Section: Methodsmentioning
confidence: 99%
“…The analgesic effects of acupuncture are likely to be correlated with the capacity of acupuncture in modulating pituitary and hypothalamic β-endorphin levels [ 8 , 44 , 76 , 88 ]. On the other hand, the analgesic and anti-inflammatory effects of β-endorphin on inflammatory pain have also been confirmed [ 27 ]. Taken together, acupuncture may play a positive role in COVID-19 associated pain.…”
Section: Methodsmentioning
confidence: 99%
“…The study found that EA analgesia was blocked by an antibody against β-endorphin and a corticotropin-releasing factor antagonist that were delivered locally in AIA rats [ 99 ]. In the same AIA model, EA at GB30 and GB34 elevated the β-endorphin levels in inflamed skin tissue and the percentage of β-endorphin immunoreactive keratinocytes, macrophages, and T-lymphocytes, which suggests that EA induces the release of peripheral opioids at the inflammatory site [ 100 ]. Accumulating evidence has indicated that opioids bind to receptors on immune cells to regulate inflammatory cytokines and thus exerting analgesic and immunomodulatory actions.…”
Section: The Mechanisms Of Macrophage Polarization Regulated By Acupuncturementioning
confidence: 99%
“…In addition, β-EP synthesized and released by immune cells under inflammatory conditions can combine to corresponding receptors on the surface of immune cells and regulate inflammatory factors [42]. Studies have shown that β-EP can selectively inhibit the expression of IL-1β and TNF-α in synovium and foot inflammatory tissues of CIA rats [17].…”
Section: Effects Of Moxibustion On the Contents Of Cxcl1 β-Ep Tnf-α And Il-1β In Ra Patientsmentioning
confidence: 99%
“…However, it is important to note that inflammation not only plays a painful role but also triggers immune cells containing opioid peptides to gather and release endogenous opioid peptide at the inflammatory site, resulting in an analgesic effect [12][13][14]. β-endorphin (β-EP), as an endogenous opioid peptide with typical opioid like effects, not only acts on opioid receptors on primary afferent neurons through secretion of immune cells, blocking pain transmission, so as to achieve analgesic effect [15], but also regulates immune function by binding to receptors on immune cells [16,17]. erefore, the changes of chemokines and endogenous opioid peptides in vivo are closely related to the disease development and clinical symptoms of RA patients.…”
Section: Introductionmentioning
confidence: 99%